2011
DOI: 10.1111/j.1600-0765.2010.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo behavior of complete human oral mucosa equivalents: characterization in athymic mice

Abstract: The present study shows the potential regenerative capacity of the CAOMEs by their ability to reach maturity similar to that seen in oral mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…In our work, we employed a fibrin-agarose scaffold that overcomes the drawbacks of both the animal-derived and the synthetic biomaterials used in other studies, such as the biocompatibility, biodegradability, fibroblastic infiltration capacity, morphologic and mechanical stability, and feasibility of an autologous source (17). Moreover, in comparison with other fibrin-based scaffolds previously reported (2,3,20), the fibrin-agarose improves the rheological stability while maintaining the viscoelastic properties of the native tissue (21). The construction of a human oral mucosa substitute intended for clinical application should ideally employ cells and biomaterials derived from the patient to avoid immunological concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, we employed a fibrin-agarose scaffold that overcomes the drawbacks of both the animal-derived and the synthetic biomaterials used in other studies, such as the biocompatibility, biodegradability, fibroblastic infiltration capacity, morphologic and mechanical stability, and feasibility of an autologous source (17). Moreover, in comparison with other fibrin-based scaffolds previously reported (2,3,20), the fibrin-agarose improves the rheological stability while maintaining the viscoelastic properties of the native tissue (21). The construction of a human oral mucosa substitute intended for clinical application should ideally employ cells and biomaterials derived from the patient to avoid immunological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial layer plays a major function as a barrier against external aggressions such a physical damage, bacterial infection, heat loss and ionizing radiation. The epithelial tissue consists of several layers of keratinocyte cells undergoing constant differentiation and self‐renewal, and recent studies focused on the role that key proteins and biological regulators such as cytokeratins, basement membrane proteins and intercellular junction proteins play in this process . However, these studies have not been carried out on artificial oral mucosa (AOM) substitutes developed by tissue engineering.…”
mentioning
confidence: 99%
“…In vivo animal studies have been carried out to investigate the role of grafted tissue-engineered oral mucosa in wound healing. Pena et al (2011) evaluated an autologous fibrin glue-based engineered oral mucosa by subcutaneous implantation in athymic mice. Although the results of their study showed that the epithelium remained viable and expressed a cytokeratin profile similar to that of native oral mucosa, it may be difficult to extrapolate the data to the clinical situation, where wounds are left open and the grafted material is air-exposed.…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%
“…Fibrin is an ideal matrix because it can stimulate fibroblast proliferation while preserving the epidermal cell “sternness” (Del Rio et al, 2002). Once it is transplanted, fibrin matrix is replaced by collagen fibers synthesized de novo by the embedded fibroblast population and forms tissue histologically similar to a natural lamina propria (Peña et al, 2011).…”
Section: Discussionmentioning
confidence: 99%